Holly the Christmas fairy - "Meadows, Daisy" (orchard books: London, 2017)
"Holly the Christmas Fairy puts the sparkle into Christmas! But Jack Frost has stolen Santa's sleigh, and now the queen of the fairies needs Rachel and Kirsty to help get it back"--Page 4 of cover
Keywords: Christmas fiction Fairies